2017
DOI: 10.1002/ejoc.201700646
|View full text |Cite
|
Sign up to set email alerts
|

Activated Glycerol Carbonates, Versatile Reagents with Aliphatic Amines: Formation and Reactivity of Glycidyl Carbamates and Trialkylamines

Abstract: International audienceno abstrac

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…This proton is deshielded from 3.5 to 4.9 ppm, which can be attributed to the close proximity of the carbamate moiety (Scheme , proton k ). This observation is in agreement with our previous work where it has been shown that this type of proton is indeed at around 5 ppm . The lower integration of this signal indicates that this transfer reaction is in minority, corresponding roughly between one-fourth and one-third of the oligomerization process.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…This proton is deshielded from 3.5 to 4.9 ppm, which can be attributed to the close proximity of the carbamate moiety (Scheme , proton k ). This observation is in agreement with our previous work where it has been shown that this type of proton is indeed at around 5 ppm . The lower integration of this signal indicates that this transfer reaction is in minority, corresponding roughly between one-fourth and one-third of the oligomerization process.…”
Section: Resultssupporting
confidence: 93%
“…From previous results within the group, the synthesis of N , N- glycidyl carbamates 1 (Scheme ) is a three-step process starting from glycerol carbonate 2 , a renewable molecule. It involves the activation of the primary alcohol as a sulfonate using tosyl chloride to form the tosylated glycerol carbonate 3 . This cyclic carbonate then reacts with a primary or a secondary amine, leading to the formation of the carbamate function.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations